2016
DOI: 10.1259/bjr.20150823
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced ultrasound (CEUS) in blunt abdominal trauma

Abstract: Baseline ultrasound is essential in the early assessment of patients with a huge haemoperitoneum undergoing an immediate abdominal surgery; nevertheless, even with a highly experienced operator, it is not sufficient to exclude parenchymal injuries. More recently, a new ultrasound technique using second generation contrast agents, named contrast-enhanced ultrasound (CEUS) has been developed. This technique allows all the vascular phase to be performed in real time, increasing ultrasound capability to detect par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
92
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(93 citation statements)
references
References 62 publications
(75 reference statements)
0
92
0
1
Order By: Relevance
“…This helps achieve the correct diagnosis and recognize some complications occurring in the acute setting, and it also prevents possible disabilities due to a delayed diagnosis in the chronic setting. [59][60][61] These pathologic entities usually occur with the same predictable patterns, mainly because of the presence of open physes and apophyseal ossification centers in children, and in some cases they have a typical radiographic appearance. When in doubt a comparative study or a MRI should be performed to avoid adjunctive radiation exposure, especially in the chronic setting.…”
Section: Resultsmentioning
confidence: 99%
“…This helps achieve the correct diagnosis and recognize some complications occurring in the acute setting, and it also prevents possible disabilities due to a delayed diagnosis in the chronic setting. [59][60][61] These pathologic entities usually occur with the same predictable patterns, mainly because of the presence of open physes and apophyseal ossification centers in children, and in some cases they have a typical radiographic appearance. When in doubt a comparative study or a MRI should be performed to avoid adjunctive radiation exposure, especially in the chronic setting.…”
Section: Resultsmentioning
confidence: 99%
“…injuries, particularly in hemodynamically stable patients with isolated blunt low or moderate-energy abdominal trauma [8][9][10][11]. Some previous studies showed that CEUS can detect active bleeding [12,13] and that performing one or two CEUS during follow-up is useful [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…The use of CEUS to detect intraand extra-parenchymal active bleeding, which is seen as http: //www.openveterinaryjournal.com P. Di Donato et al Open Veterinary Journal, (2019), Vol. 9(4): 309-312 extravasation/pooling of microbubbles or hyperechoic bands, has been described in medicine (Miele et al, 2016). This technique, when compared to cystoscopy or even cystotomy, is a safe and non-invasive alternative that does not require general anesthesia, endoscopic equipment, or extensive training.…”
Section: Case Detailsmentioning
confidence: 99%